Spray-dried tomato powder: reconstitution properties and colour - Sousa,Alexandre Santos de (2008)
Powdered tomato was produced by spray drying the tomato pulp. A full 2³ factorial design with the central point was used, varying the feed flow rate (127-276 g/min), air inlet temperature (200-220ºC) and the atomisation speed (25,000-35,000 rpm). The responses analysed were: moisture content, solubility, wettability consistency and colour, but the factors only significantly affected the colour parameter. All the samples became significantly darker and less red with an increase of the variables under study. A low atomisation speed (25,000 rpm) and lower inlet air temperature (220ºC) produced the powders with a higher colour index (a/b) and less darkening.